2004
DOI: 10.1161/01.hyp.0000146400.57221.74
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Angiotensin-Converting Enzyme 2 by All- trans Retinoic Acid in Spontaneously Hypertensive Rats

Abstract: Abstract-There is increasing evidence that all-trans retinoic acid (atRA) influences gene expression of components of renin-angiotensin system (RAS), which plays a pivotal role in the pathophysiology of essential hypertension. To further validate effects of atRA on the RAS and to assess the possibility that atRA affects the activity of angiotensin-converting enzyme 2 (ACE2), gene, and protein expression of ACE2 have been examined by real-time polymerase chain reaction and Western blot methods in spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 39 publications
4
114
1
3
Order By: Relevance
“…These results are in concordance with our previous study, in which we found that ATRA treatment was associated with reduced expression of ACE1 and increased expression of ACE2 in glomerulosclerosis rats. 7 Furthermore, Zhong et al 23 reported that chronic ATRA treatment increased both gene and protein expression of ACE2, which resulted in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats. ATRA was associated with up-regulated expression of ACE2, and their results and conclusion were similar to ours, albeit in a different cell type.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in concordance with our previous study, in which we found that ATRA treatment was associated with reduced expression of ACE1 and increased expression of ACE2 in glomerulosclerosis rats. 7 Furthermore, Zhong et al 23 reported that chronic ATRA treatment increased both gene and protein expression of ACE2, which resulted in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats. ATRA was associated with up-regulated expression of ACE2, and their results and conclusion were similar to ours, albeit in a different cell type.…”
Section: Discussionmentioning
confidence: 99%
“…The result is not consistent with the previous reported that heart ACE2 mRNA and protein expressions were markedly decreased in spontaneously hypertensive rats when compared with WKY rats. 41) However, Gallagher et al showed that myocyte treatment with inhibitors of myocyte and cardiac fibroblast growth, such as Ang-(1-7) or atrial natriuretic peptide reversed the ACE2 mRNA downregulation by hypertrophic hormones like Ang II or ET-1, indicated that ACE2 expression in the heart was dependent upon the regulation and concentration of multiple hypertrophic and anti-hypertropic peptides. 42) Thus the discrepancy may due to the different induced factor of cardiac hypertrophy; high BP in previous study and high BPV in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ACE2 expression can be induced by retinoic acid (vitamin A). Functionally, induction of ACE2 expression by retinoic acid is associated with reduction in blood pressure in spontaneously hypertensive rats (31).…”
Section: Ontogeny Of Ace2mentioning
confidence: 99%